Binding of extracellular matrix proteins to Paracoccidioides brasiliensis - Mendes-Giannini, Maria José Soares [UNESP]; Andreotti, Patricia Ferrari; Vincenzi, Luciana Raquel; Monteiro da Silva, Juliana Leal; Lenzi, Henrique Leonel; Benard, Gil; Zancope-Oliveira, Roseli; Leonel de Matos Guedes, Herbert; Soares, Christiane Pienna (Elsevier B.V., 2006)
Adhesion to extracellular matrix (ECM) proteins plays a crucial role in invasive fungal diseases. ECM proteins bind to the surface of Paracoccidioides brasiliensis yeast cells in distinct qualitative patterns. Extracts from Pb18 strain, before (18a) and after animal inoculation (18b), exhibited differential adhesion to ECM components. Pb18b extract had a higher capacity for binding to ECM components than Pb18a. Laminin was the most adherent component for both samples, followed by type I collagen, fibronectin, and type IV collagen for Pb18b. A remarkable difference was seen in the interaction of the two extracts with fibronectin and their fragments. Pb18b extract interacted significantly with the 120-kDa fragment. Ligand affinity binding assays showed that type I collagen recognized two components (47 and 80 kDa) and gp43 bound both fibronectin and laminin. The peptide 1 (NLGRDAKRHL) from gp43, with several positively charged amino acids, contributed most to the adhesion of P. brasiliensis to Vero cells. Synthetic peptides derived from peptide YIGRS of laminin or from RGD of both laminin and fibronectin showed the greatest inhibition of adhesion of gp43 to Vero cells. In conclusion, this work provided new molecular details on the interaction between P. brasiliensis and ECNI components. (c) 2006 Elsevier SAS. All rights reserved.
Keywords: Paracoccidioides brasiliensis; extracellular matrix; adhesins; gp43